THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY GOAL, CORPORATE SOCIAL ISSUE, AND CORPORATE RELATION PROGRAM OF PT. SEMEN GRESIK TO SOCIAL WELFARE - ROSYIDI, AMIRUL AFFAN (Jurnal Ilmiah Mahasiswa FEB, 2016)
Nowadays,  companies  are increasingly  developed,  which is at the same time  increasing   the  social  gap  and  the  surrounding   environmental   damage. Therefore, it is urgent to increase the awareness to reduce these negative impacts through Corporate Social Responsibility of the related companies. The objective of this study is to determine the effect of variables corporate social responsibility to social welfare around Gresik by analyzing the influence of CSR  variables  consisting  of  items:  CSR  goals,  corporate  social  issues,  and corporate programs related to community well-being in Gresik. The sample of the study is selected  using purposive  sampling  technique  with 59 respondents  who receive  assistance  from  PT  Semen  Gresik  CSR.  To  collect  the  data,  survey methods is used in the form of explanatory research. The primary research data is questionnaires,  while the secondary  data are related  literature,  internet  sources, and interviews. The collected then is sort and analyzed using a Likert scale, while test the validity and reliability  is conducted  using statistical  crosstabs  by SPSS 16.0 software. Based on multiple linear regression analysis the results using the t test, it can be concluded that the corporate variables related programs partially affect the social   live  welfare.   While,   based  on  the  results   of  the  standardized   Beta Coefficients  respectively, it is revealed that corporate variables related programs pose dominant influence on the welfare of the community Gresik. So, the result is from Variabel CSR (Corporate Social Responsibility Goal, Corporate Social Issue, Corporate  Related  Program)  does  not  have  significance  effect  to  social  live welfare around PT Semen Gresik..   Keywords;  CSR  goals,Corporate  Social  Issue,    Corporate  Relation  Program, Social Welfare